Evaluation of Islamic Religious Education Learning Based on Local Wisdom - Subhan, Subhan; Isnah, Isnah; Muslimah, Muslimah (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This research aims to analyze the evaluation of learning based on Islamic Religious Education (PAI). This research is included in the type of library research, namely research that analyzes content related to the opinions of experts and researchers that have been published regarding the evaluation of learning in PAI subjects based on local wisdom. Secondary data sources were obtained through books and journal articles as well as other sources relating to the policies of the government of the Republic of Indonesia regarding PAI curriculum and learning. Selecting literature that is relevant to the content of this research, namely evaluation of PAI and local wisdom-based learning, as well as the implementation of both in learning. Next, analyze the literature to assess the extent to which it provides an understanding of the evaluation of PAI learning based on local wisdom. Aims to determine the suitability of the concept and application of local wisdom-based learning for PAI teachers. The findings of this research are that local wisdom-based PAI learning evaluations have a positive impact in achieving learning goals, helping teachers and educational institutions understand the strengths and weaknesses of learning, so they can continue to improve the process. The integration of local wisdom in PAI learning does not only focus on cognitive aspects, but also builds strong morals and culture in students, not only serves to assess the effectiveness of materials and methods, but also to understand the extent to which students can link religious values with the culture they live in. The results of this evaluation will provide valuable information for teachers in achieving PAI learning goals